The Relationship Between Parenting Patterns and The Independence of Alpha Generation School-Age Children at SD X Jakarta. - Aprillia Rohmana; Rima Berlian Putri; Maria Susila Sumartiningsih; Roza Indra Yeni (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Background: generational change is a natural consequence of the dynamics of modern development, requiring parents to adapt their parenting styles to meet the needs of Generation Alpha school-age children. This study aims to determine the relationship between parenting styles and the level of independence of Generation Alpha school-age children. This research method used a quantitative correlational cross-sectional approach, with variables measured only once. The population in this study was all Generation Alpha students at Elementary School X Jakarta, with a sample size of 52 students drawn using total sampling. Data were collected using a questionnaire and analyzed using descriptive statistics. The instrument contained 52 indicators representing the three parenting styles on aspects of child independence. The results of the study, using the Chi-Square Test with Likelihood Ratio, showed a significant correlation of 8.795 with p=0.012 > 0.05. Therefore, it can be concluded that there is a significant relationship between parenting styles and the independence of Generation Alpha school-age children at Elementary School X. Generation Alpha demonstrates unique independence, thus parenting styles play a crucial role in supporting the independence of Generation Alpha school-age children.